CARBON LAYER PENETRATION AS A FAILURE CRITERION FOR TITANIUM METAL MATRIX COMPOSITES REINFORCED WITH CARBON COATED SiC FIBRES - Tesha, J. V. (Tanzania Journal of Engineering and Technology, 2018)
Abstract